Gamification as a Strategy to Enhance Learning Motivation and Argumentative Writing Skills of Eleventh Grade Students at SMA Negeri 1 Sidrap. - Rosmini Kasman; Fadlina; Hamdi M. Daming (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
The low level of learning motivation and inadequate skills in writing argumentative texts remain major challenges in Indonesian senior high school education. This study investigates the effectiveness of gamification as an innovative strategy to enhance both learning motivation and argumentative text writing skills among grade XI students at SMA Negeri 1 Sidrap. A quasi-experimental design with one-group pretest-posttest was employed. The sample consisted of 35 students from one intact class (out of nine classes/rooms in the relevant grade level). Gamification elements such as points, badges, leaderboards, levels, quests, and immediate feedback were integrated into argumentative writing lessons over eight meetings using a digital learning platform combined with classroom activities. Data were collected through a validated learning motivation questionnaire (based on the ARCS model) and an argumentative text writing test assessed using a holistic rubric covering content, organization, language use, and mechanics. Paired-sample t-test results revealed a statistically significant improvement in both variables. Students’ learning motivation scores increased substantially (p < 0.05), and their argumentative writing skills improved from an average pretest score of 64.57 to 82.86 in the posttest. Qualitative observations further indicated higher student engagement, collaboration, and persistence during gamified sessions. The findings demonstrate that gamification is an effective pedagogical strategy that simultaneously boosts affective (motivation) and cognitive (writing skills) outcomes. This approach offers practical implications for language teachers seeking to create more engaging and student-centered learning environments in senior high schools.